A multidisciplinary approach for the quantitative provenance analysis of siltstone. Mesozoic Mandawa Basin, southeastern Tanzania - Caracciolo, Luca; Andò, Sergio; Vermeesch, Pieter; Garzanti, Eduardo; McCabe, Ross; Barbarano, Marta; Paleari, Chiara; Rittner, Martin; Pearce, Timothy (Journal of the Geological Society, 2019)
This paper shows how heavy minerals and single-grain varietal studies can be conducted on silt (representing 50% of world’s sediments) sediments to obtain quantitative data as efficiently as for sand-sized sediments. The analytical workflows include heavy mineral separation using a wide grain-size window (15-355 μ) analysed through integrated optical analysis, RAMAN spectroscopy, QEMSCAN microscopy, U-Pb dating of detrital zircon. Upper Jurassic-Cretaceous silt-sized sediments from the Mandawa basin of central-southern Tanzania have been selected for the scope of this research. Raman-aided heavy mineral analysis reveals garnet and apatite to be the most common minerals together with durable zircon, tourmaline and subordinate rutile. Accessory but diagnostic phases are titanite, staurolite, epidote, and monazite. Etch pits on garnet and cockscomb features on staurolite document the significant effect of diagenesis on the pristine heavy mineral assemblage. Multivariate statistical analysis highlights a close association among durable minerals (zircon, tourmaline and rutile, ZTR) while garnet and apatite plot alone reflecting independence between the three group of variables with garnet increasing in Jurassic samples. Raman data for garnet end-member analysis document different associations between Jurassic (richer in A, Bi and Bii types) and Cretaceous (dominant A, Ci and Cii types) samples. U-Pb dating of detrital zircon and their statistical integration with the above mentioned datasets provide further insights on changes in provenance and/or drainage systems. Metamorphic rocks of the early and late Pan-African orogeny terranes of the Mozambique belt and those of the Irumide Belt acted as main source of sediment during the Jurassic. Cretaceous sediments record a broadening of the drainage system reaching as far as the Usagran-Ubendian Belt and the Tanzanian Archean Craton.<br
Keywords: Provenance analysis; silt sediments; Tanzania; Mandawa Basin

A Quantitative Provenance Analysis (QPA) Approach to Quantify Controls on Sediment Generation and Sediment Flux in the Upper Reaches of the Magdalena River (Colombia): 1. Natural and Anthropic Controls on the Sand Fraction - Liedel, Stefan; Caracciolo, Luca; Restrepo, Juan Camilo; Weltje, Gert Jan; Lucà, Federica; Beltrán‐Triviño, Alejandro; Restrepo Ángel, Juan Darío (Journal of Geophysical Research F: Earth Surface, 2024)
This study investigates the upper Magdalena river basin (Colombia), which is characterized by tectonic activity, tropical climate, heterogeneous lithological assemblages, and anthropic influence. It aims to comprehend factors controlling sediment generation, flux, and composition by incorporating petrographic data from 27 recent fluvial samples along with geochemistry, geomorphological parameters, historical precipitation, land cover, landsliding and suspended sediment load data. The analysis shows mismatches between sand composition and drainage lithology distribution. A new set of endmember mixing models is presented, quantifying the impacts of erodibility, sand generation potential (related to lithology), and sediment connectivity between hillslopes and river outlets (related to geomorphology). Results show enhanced sediment generation from sedimentary rocks (up to 40%) due to high erodibility, and decreased sediment flux from low- to medium-grade metamorphic rocks (up to 60%) due to controlling morphometric parameters. Overrepresentation of plutonic and high-grade metamorphic rocks and underrepresentation of volcanic rocks (up to 100%) are controlled by mineralogical and textural parameters. Enhanced landsliding activity in areas with volcanic activity occasionally overshadows basin-wide compositional trends driven by morphological and lithological characteristics, as it controls rare overrepresentation of volcanic and low-grade metamorphic detritus in the sand fraction. Sediment retention by hydroelectric dams significantly decreases suspended sediment flux by 30%, while deforestation plays a minor role in sediment flux. This study underscores the importance of coupling sediment generation, geomorphology and the distribution of stochastic events related to seismic activity in any sediment production-focused study and for developing numerical models in Quantitative Provenance Analysis (QPA
Keywords: Sediment generation; Quantitative provenance analysis; Hillslope geomorphology; Index of Connectivity; Anthropogenic effect; Sediment budget

A Quantitative Provenance Analysis (QPA) Approach to Quantify Controls on Sediment Generation and Sediment Flux in the Upper Reaches of the Magdalena River (Colombia): 2. Lithological Control on Contribution to Silt‐ to Clay‐Sized Fractions - Liedel, Stefan; Caracciolo, Luca; Beltrán‐Triviño, Alejandro; Restrepo, Juan Camilo; Restrepo Ángel, Juan Darío; Szczerba, Marek (Journal of Geophysical Research F: Earth Surface, 2024)
The composition of 27 fluvial silt and clay sediments was used in this study to identify and quantify the processes in the upper valley of the Magdalena river in South Colombia. The combination of seismic activity, intense precipitation, and landsliding resulted in limited chemical weathering and a very efficient transfer of weathered products to the transfer zone of both tributary rivers and the main trunk. Inputs from plutonic, high-grade metamorphic, volcanic, and low- to medium-grade metamorphic lithologies vary in coarse silt-sized versus fine silt- and clay-sized sediments, reflecting inherited textural parameters and mineralogy. Plutonic and high-grade metamorphic rocks mostly produce sand-sized sediments, up to two times more than coase silt and up to 10 times more than fine silt to clay. The prevalence of siltstone in the area enhances the contribution of sedimentary rocks to fine silt and clay (up to 50% higher than to sand). Volcanic rocks mainly produce coarse silt (up to 2.5 times more than sand). Low-grade metamorphic detritus is enriched in silt and clay (up to 5–7 times). These findings highlight the critical role of lithology in regulating sediment generation. The study's approach can establish or modify factors modeling lithological control on suspended sediment flux, such as in the BQART equatio
Keywords: Sediment generation; Quantitative provenance analysis; Sediment budget; Lithological control; Linear mixing model; Raman light and heavy mineral analysis

Burial of a sand sea: Heterogeneous compaction and cementation of the jurassic Etjo Formation, Namibia and what it tells - Salomon, Eric; Stollhofen, Harald; Caracciolo, Luca; Bonnell, Linda M.; Lander, Robert H.; Kittel, Mario (Marine and Petroleum Geology, 2024)
Aeolian sandstones are capable of forming excellent reservoir rock due to their textural and compositional maturity. Often spanning across large areas, such formations may however experience spatial variability in burial and temperature exposure potentially leading to a heterogeneous diagenesis and subsequent reservoir quality. To assess such potential variability, this case study focusses on the diagenesis of the aeolian units of the Lower Jurassic Etjo Formation in Namibia, exposed at three key localities lying >100 km apart from each other. The Etjo Formation has experienced two major burial phases controlled by the emplacement of (I) Jurassic Karoo and (II) Lower Cretaceous Paraná-Etendeka volcanic rocks separated by an intervening exhumation phase. Petrographic analysis reveals very different rock properties between the localities with respect to intergranular volumes (IGV), intensity of quartz cementation, and preserved porosities. Average IGV and quartz cement values are 30.7 % and 24.3 % at Gamsberg, 23.7 % and 6.5 % at Waterberg and 19.7 % and 15.4 % at Mt. Etjo. Point-counted intergranular porosity values are on average 2.6 % (Gamsberg), 10.8 % (Waterberg), and 1.5 % (Mt. Etjo). Waterberg samples had an on average 72 % larger nucleation surface area available for quartz cement growth than samples from Mt. Etjo. The higher quartz cement volumes at Mt. Etjo therefore argue for a higher thermal exposure than at Waterberg. This is supported by kaolinite-to-illite transformation only occurring at Mt. Etjo. We attribute the higher temperature signature to the proximity of Mt. Etjo to the center of lower Cretaceous Paraná-Etendeka volcanism and related elevated thicknesses of the lava pile or heat flow increase. At Gamsberg, there is evidence for a quartz cement generation that formed during the Jurassic. This earlier cement stabilized the grain framework and preserved the IGV during the following Etendeka burial event. The Etjo Formation provides an exceptional example for the wide range of very low to very high degrees of compaction and cementation that can occur within an otherwise homogeneous, texturally and compositionally mature sandstone formation. This study underscores the importance of accounting spatial variations in burial depths and temperatures when predicting the diagenetic properties of reservoir rocks.<br
Keywords: Sandstone diagenesis; Quartz cementation; Compaction; Intergranular volume; Paraná-Etendeka Large Igneous Province; Aeolian sandstone

Climatic, depositional and environmental controls on early carbonate cementation in fluvial and shallow marine sandstones - Janßen, Meike; Caracciolo, Luca; Bonnell, L. M.; Lander, R. H.; Munnecke, Axel; Beltrán-Triviño, A.; Muto, F.; Stollhofen, Harald (Marine and Petroleum Geology, 2023)
Sandstones with carbonate cements are found in a variety of depositional settings (e.g. fluvial, lacustrine, deltaic, shallow marine) with abundances ranging from just a few volume percent to pervasive pore-filling cements and are of major interest due to their impact on reservoir quality. Despite the widespread occurrence of such cements, predictive models for eogenetic carbonate cementation have yet to be developed. Hence, investigations on the controls and distribution of early carbonate precipitation are necessary to improve the accuracy of predictions of the nature and distribution of diagenetic alterations. We conducted a petrological and petrophysical analysis of early near-surface carbonate cementation in siliciclastic and mixed siliciclastic-carbonate sandstones from fluvial and shallow marine environments to reconstruct eogenetic processes and their associated controls. Furthermore, sediment burial scenarios up to a loading of 50 MPa were simulated with the reservoir quality prediction software Touchstone to evaluate the impact of carbonate cements on the compaction behaviour of the rocks. Results highlight the importance of climate, depositional environment and detrital composition and texture in regards to the precipitation processes of near-surfaces carbonate cements and burial development. Our data shows that the presence and distribution of early carbonate cements reflects a complex interaction of several parameters, such as the composition and texture of detrital material in the source area, the availability and infiltration of meteoric or marine waters and the presence of precursor carbonate during deposition. Burial simulations demonstrate the strengthening effect of early carbonate cementation and its influence on the development of intergranular volume and porosity during burial with up to five times less porosity loss due to compaction than without near-surface cementation.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Carbonate cementation; Intergranular volume; Mixed siliciclastic-carbonate sediments; Near-surface diagenesis; Reservoir quality

Comment on Maravelis et al. “Accretionary prism–forearc interactions as reflected in the sedimentary fill of southern Thrace Basin (Lemnos Island, NE Greece)” - Caracciolo, Luca; et al. (International Journal of Earth Sciences, 2017)

Corrigendum to “Disequilibrium compaction overpressure in shales of the Bavarian Foreland Molasse Basin: Results and geographical distribution from velocity-based analyses” [Mar. Pet. Geol. 92 (2018) 37–50](S0264817218300618)(10.1016/j.marpetgeo.2018.02.017) - Drews, Michael; Bauer, Wolfgang; Caracciolo, Luca; Stollhofen, Harald (Marine and Petroleum Geology, 2019)
The authors regret that the following mistakes in the description and graphical representation of the normal compaction trend (NCT) have been erroneously carried forward by the authors from an earlier version of the manuscript to the final version of the manuscript, which does not allow for reproduction of the normal compaction trend used in the study: 1. For all pressure analyses conducted in the study, the constant exponent n of equation (3) has been set to 2.0, instead of 2.19. Therefore, paragraph 1 on page 41 should be read as “[…] which we set to a value of 2.0 for shale, similar to Issler (1992).”2. The vertical stress, necessary to calculate the NCT as represented in Figs. 4, 5 and 6, has been erroneously calculated with a phi0-parameter of 0.35 instead of 0.3 (compare equation (2) and table 1). For the three green data points (Oligocene Normal Pressure, NW-Molasse) of Fig. 5 we spotted an additional minor error in the calculation routine of the vertical effective stress. We attached the corrected figures to the end of this corrigendum.We would like to emphasize that the errors have not been carried forward in the remainder of the study and manuscript. The corrections are only necessary to being able to reproduce the used normal compaction trend, but do not affect any of the results, conclusions or any other figures or written passages of the manuscript. The authors would like to apologize for any inconvenience caused. [Figure presented] Fig. 4. Shale velocities vs. true vertical depth (TVD) for normally pressured Oligocene (yellow and green dots) and Mesozoic shales (blue dots). Oligocene shales from wells in the north-western Bavarian Foreland Molasse Basin (wells marked by green dotted envelope on the map inset and green dots on the velocity-depth plot) generally have faster velocities, which might be attributed to more heterolithic sequences and/or increased uplift. The calculated normal compaction trend (NCT) derived from the combination of the modified Athy equation and the porosity-velocity transform of Raiga-Clemenceau et al. (1988) is represented by the black dashed line. [Figure presented] Fig. 5. Vertical effective stress vs. shale velocity relationship from both normally pressured and overpressured wells. Vertical effective stress values have been derived from drill stem and production tests and wireline formation pressure tests and associated shale velocities are captured from sonic and VSP data from adjacent shale sequences. The dashed black curve represents the normal compaction trend (NCT) established for the Bavarian Foreland Molasse Basin. [Figure presented] Fig. 6. Shale velocities compiled from seismic (VSP) and sonic velocities vs. true vertical depth (TVD) for both normally pressured and overpressured Oligocene and Mesozoic (Cretaceous and Jurassic) shales. Velocities from overpressured Oligocene and Cretaceous shales clearly depart from the normal compaction trend around 2500 m, with some minor diversions even in shallower sections.
CRIS-Team Scopus Importer:2019-12-03

Depositional controls on sediment properties in dryland rivers: Influence on near-surface diagenesis - Henares, Saturnina; Donselaar, Eric Marinus; Caracciolo, Luca (Earth-Science Reviews, 2020)
Sandy braided dryland rivers, deposited under arid to semi-arid conditions, constitute important clastic reservoirs worldwide whose reservoir quality reflects the effect of primary sediment properties on near-surface diagenetic processes. A literature review is presented of existing facies models, based on geomorphological analysis of modern perennial braided rivers, further illustrated with own outcrop and subsurface examples of dryland river deposits in: (a) Argana Basin (Triassic, Morocco), (b) Iberian Meseta (Triassic, Central SE Spain), (c) Huesca Fluvial Fan (Miocene, Spain) and (d) Rotliegend hydrocarbon reservoir in the Southern Permian Basin (The Netherlands). The facies models, combined with the analyses of the rock record, provides a comprehensive depositional framework where the influence of depositional characteristics, such as grain-size and sorting variations, interstitial clay distribution and composition and amount of intrabasinal components, on the extent and pathway of near-surface mechanical and chemical processes can be investigated. The particular dryland setting is characterized by prolonged periods of inactivity and short, episodic periods of peak discharge, which lead to the transport and deposition of poorly-sorted, clay-rich extra- and intraformational conglomeratic sediments upstream. Downstream, channels, mid-channel and bank-attached bars develop with conspicuous anisotropic trough and tabular cross-stratified sandstones. The most common near-surface diagenetic processes that alter the textural properties of these deposits are the rapid decrease of porosity and permeability due to grain-rearrangements and mechanical compaction of mud intraclasts along with pervasive early carbonate cementation. The results of this study will help to better configure the boundary conditions (e.g., external versus local supply for carbonates cements) in state-of-the-art reservoir quality forward models for ancient dryland river sandstones, which are especially prominent in Devonian, Permian, Triassic and Jurassic reservoir setting

Diagenetic constraints on heterogeneous reservoir quality assessment: A Triassic outcrop analog of meandering fluvial reservoirs - Caracciolo, Luca; et al. (Aapg Bulletin, 2016)
Reliable modeling of meandering fluvial reservoirs is challenging because of the heterogeneity in magnitude and pattern of porosity and permeability related to depositional and diagenetic features. Early mechanical and chemical alterations proceed along different pathways directly related to depositionally governed differences in textural and compositional parameters. In a well-constrained sedimentological framework and with relatively homogeneous conditions of detrital composition, this study aims to determine the effect of depositional fabric on early diagenetic processes and their collective effect on petrophysical properties (pore size distribution, open porosity, and permeability). A high-resolution qualitative and quantitative petrographic analysis is conducted on 22 fine-to very fine-grained sandstones from the main meandering fluvial facies of the channel (center and margin), point bar (lower, middle, and upper), scroll bar, and chute channel of a Triassic outcrop analog. The occurrence of small-scale internal heterogeneity associated with detrital matrix and suspension settling laminae favors the compaction process and hinders early pore-filling cement precipitation that helps the preservation of primary porosity. Multivariate statistical treatment of data demonstrates that large (>1 mu m) and well-connected primary inter granular pores are the main contributors to permeability in the more heterogeneous samples. The distribution of the finer-grained sediment fraction is strongly facies related as a result of hydraulic sorting. Better understanding of linkages between depositionally predictable features and diagenetically induced heterogeneity may lead to realistic reservoir models and enhanced effectiveness of exploitation and bypassed-oil recovery strategies.

Disequilibrium compaction overpressure in shales of the Bavarian Foreland Molasse Basin: Results and geographical distribution from velocity-based analyses - Drews, Michael; Bauer, Wolfgang; Caracciolo, Luca; Stollhofen, Harald (Marine and Petroleum Geology, 2018)
<span style="color: rgb(46, 46, 46); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: 16px; word-spacing: -1.24453px;">Shale velocity data from sonic logs and vertical seismic profiles, drilling data and <em style="border: 0px; font-size: 16px; margin: 0px; padding: 0px; vertical-align: baseline; font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; color: rgb(46, 46, 46); word-spacing: -1.24453px;">in situ<span style="color: rgb(46, 46, 46); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: 16px; word-spacing: -1.24453px;">pressure measurements from a total of 116 wells have been analyzed to gain an improved understanding of the lateral and vertical distribution and formation of overpressure in the Bavarian Foreland Molasse Basin. Pore pressure from sonic and vertical seismic profile velocities has been analyzed by establishing a normal compaction trend for Cenozoic and Mesozoic shales combined with a classical Eaton approach. The study demonstrates that a single shale normal compaction trend for the Bavarian Foreland Molasse Basin is sufficient to estimate pore pressure and thus overpressure from sonic and vertical seismic profile velocity. Maximum overpressure develops at depths between 1500 and 2500 m and increases with depth at a constant effective stress of 20 MPa. The strong dependency of overpressure on burial depth, constant effective stress and restriction to shale units that are overlain by sequences with very high sedimentation rates indicates that disequilibrium compaction is the main cause for overpressure. Also, variable presence of Cretaceous shales is a key control of overpressure occurrence in Oligocene shales in the Bavarian Foreland Molasse Basin, since Cretaceous shales likely act as a “pressure buffer” to underpressured Mesozoic carbonates. Successful detection and prediction of overpressure from vertical seismic profile data is encouraging for future pre-drill prediction of overpressure from velocity data of seismic surveys in the Bavarian Foreland Molasse Basin, resulting in improved well planning, reliable calculation of project costs, and improved safety during drilling activities in the Bavarian Foreland Molasse Basin. The presented overpressure distributions will be a key input for future geomechanical, basin and reservoir modelling studies in the Bavarian Foreland Molasse Basin.
Keywords: North Alpine Foreland Basin; Bavarian Foreland Molasse Basin; Overpressure; Pore pressure; Seismic velocity; Shale

Dispersal pathways in the early Messinian Adriatic foreland and provenance of the Laga Formation (Central Apennines, Italy) - Stalder, Nadja Franziska; Fellin, Maria Giuditta; Caracciolo, Luca; Guillong, Marcel; Winkler, Wilfried; Milli, Salvatore; Moscatelli, Massimiliano; Critelli, Salvatore (Sedimentary Geology, 2017)
Keywords: Adamello; Central Alps; Detrital zircon fission-track dating; Paleogeographic reconstruction; Sedimentary provenance; U-Pb dating

Documenting a coastal sediment routing tract in the sedimentary record: Implications for coastal palaeogeography and sand distribution patterns - Isla, Manuel; Schwarz, Ernesto; Caracciolo, Luca; Remírez, Mariano Nicolas; Veiga, Gonzalo D.; Finzel, Emily (Sedimentology, 2025)
Coastal sediment transport, primarily driven by littoral drift, is a well-understood process occurring in many wave-dominated modern coasts. This transport can extend over hundreds of kilometres, linking river mouths to sand barriers and coastal dunes. Recognizing the importance of coast-parallel processes in dispersing significant sediment volumes, both source-to-sink and sediment-routing-system concepts emphasize the need to include these processes in comprehensive studies. These processes can lead to volume changes and provenance mixing within specific source-to-sink budgets and should consider sediments near the coast and on the shelf as temporary repositories before their final transit into deep-water sinks. Despite the established methodologies for studying sediment routing systems, the integration of these approaches with the geological record is limited. To address this gap, this article introduces the Coastal Sediment Routing Tract as a segment within any Sediment Routing System. The Coastal Sediment Routing Tract consists of three elements: supplier(s), storage(s) and littoral drift processes. This study presents the conceptual framework for Coastal Sediment Routing Tracts, documents an ancient Coastal Sediment Routing Tract by linking deltaic and shoreface sandstones in the Hauterivian Pilmatué Member (Neuquén Basin, Argentina) and evaluates how characterizing a single Coastal Sediment Routing Tract can refine coastal palaeogeographical reconstructions. Understanding these aspects is crucial for improving mass balance calculations in source-to-sink analyses of ancient systems.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Coastal palaeogeography; coastal sediment routing tract; littoral cells; Neuquén Basin; sand distribution

Drainage and environmental evolution across the Permo–Triassic boundary in the south-east Germanic Basin (north-east Bavaria) - Ravida, Domenico C. G.; Caracciolo, Luca; Henares, Saturnina; Janßen, Meike; Stollhofen, Harald (Sedimentology, 2021)
The identification of the factors triggering continental environmental changes at the Permian–Triassic transition is of general interest as they allow a better understanding of the most controversial mass extinction of the Phanerozoic. This study investigates the environmental response to external forcings on continental successions at the south-east-margin of the Central European Basin System in Germany. Studies from this area are scarce, and its evolution is poorly understood. This work integrates high-resolution core-logging and quantitative sedimentary petrography of Middle Permian–Early Triassic successions recovered from the wells Obernsees-1 and Lindau-1. The sedimentological investigation reveals major vertical variations in the depositional settings marked by changes in grain-size trends and facies associations: (i) the progradation of mass flow/fluvial fans over sandflat environments denotes the Guadalupian–Lopingian; (ii) sabkha to shallow-marine conditions occur during the uppermost Permian; (iii) the onset of braided fluvial sequences marks the Permian–Triassic boundary; (iv) changes in fluvial style, reflecting increased river sinuosity, and aeolian deposition characterize the remaining Triassic. Environmental changes are accentuated by variations in sediment composition. Proximal deposits (for example, alluvial fan) are lithic arkoses, while more distal associations reveal arkosic composition. Detrital modes point to: (i) a high-grade metamorphic source feeding the drainage of Lindau-1 (metamorphic index, MI 441–500); and (ii) a mixed low-grade and high-grade metamorphic source (MI 277–395) feeding the Permian of Obernsees-1, passing upward to high-grade metamorphic (MI 441–500) and subordinate granitoid sources. Compositional signatures and environmental changes suggest distinct drainage evolutions regulated by upstream climate and tectonic controls. The higher plutonic clast content coeval to the onset of fluvial sedimentation and coarse-grained influxes reflects local tectonic perturbations attributed to the Early Triassic reactivation of Variscan faults. The evidence of perennial fluvial systems during the lowermost Triassic reflects wetter climate conditions in the upstream catchment area, which contradicts the common view of increased aridity at the Permian–Triassic boundary.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Central European Basin Systems; Early Triassic climate; external forcing controls; fluvial sedimentology; Permo–Triassic boundary; provenance analysis; synsedimentary tectonics

External forcing controls on sandstone diagenesis - Caracciolo, Luca; Janßen, Meike; Ravidà, Domenico; Bonnell, L.; Heins, W.; Lander, R.; Stollhofen, Harald (ResTech 2020, 2020)
CRIS-Team Scopus Importer:2020-12-18

Fluvial-aeolian sedimentary facies, Sossusvlei, Namib Desert - Feder, Amelie; Zimmermann, Robert; Stollhofen, Harald; Caracciolo, Luca; Garzanti, Eduardo; Andreani, Lois (Journal of Maps, 2018)
Aeolian sedimentary processes and corresponding facies shape the Earth’s surface and control the evolution of dune fields. The Namib Sand Sea with its Sossusvlei playa-lake is a perfect example to investigate the spatial distribution of fluvially influenced aeolian deposits. Remote sensing in combination with ground observations allowed for mapping of the facies distribution pattern of associated fluvial and aeolian sediments. Laboratory spectral signature measurements were used to further improve the separation between six groups of facies: modern aeolian sand, deflation surface, mud pool/mud drapes, heavy mineral lag, reworked fluvial–aeolian sediments, and fossil dune remnant. The best results were achieved through a supervised classification algorithm trained by field observations, a combination of Principal Component Analysis, band ratios, texture and geomorphologic indices. Consequently, a map outlining the facies distribution pattern of the Sossusvlei area at a scale of 1:10,000 was created. We propose this as a possible workflow to efficiently map and monitor desert environments and to investigate the interplay of aeolian and fluvial sediments.<br
Keywords: Sossus sand formation; world view 3; dune river interaction; modern sediments; facies mapping; Quaternary

From loose sand to sandstone: An experimental approach on early calcite precipitation in sands of siliciclastic and mixed carbonate-siliciclastic composition - Janßen, Meike; Caracciolo, Luca; Bonnell, Linda M.; Lander, Robert H.; Adelhardt, Philipp; Moldenhauer, Lara; Munnecke, Axel; van Geldern, Robert; Stollhofen, Harald (PLoS ONE, 2024)
Artificially cemented sandstones were produced to assess the impact of detrital texture and composition on the precipitation and distribution of early calcite cement, and cement-related degradation in porosity. To simulate early-calcite cementation, loose sediment of variable composition (siliciclastic and calcareous) and grain size was exposed to a calcite supersaturated solution for 35 to 58 days at 23◦C. Identification and distribution of the newly precipitated crystals was performed with high resolution 2D optical and scanning electron microscopy. The experimental results show the precipitation of grain-coating, pore-bridging and pore-filling granular calcite cement with up to 100 μm crystal size. Despite a positive correlation between the amount of detrital carbonate grains and calcite crystals, calcite cement does not preferentially nucleate on bioclast surfaces, irrespectively of their favourable mineralogy. Siliciclastic grains show high calcite cement coverage with altered feldspar, particularly plagioclase, displaying coverage of 94.3%. Grain size variations within the sand packs have influence on the precipitation pattern of calcite with coarse-grained layers (500–710 μm) showing minor calcite cementation (6.3%), while medium- (250–500 μm) to fine-grained layers (125–250 μm) comprise average calcite cement contents of 16.3% and 28.2%, respectively. The findings of this study enhance our knowledge regarding the precipitation processes of calcite in porous material with heterogeneous reacting mineral phases, shapes and pore connectivity.
CRIS-Team Scopus Importer:2024-11-08

Geomorphology and sand provenance of the Tyrrhenian coast between Capo Suvero and Gizzeria (Calabria, southern Italy) - Caracciolo, Luca; et al. (Rendiconti Online Societa Geologica Italiana, 2012)
Keywords: Calabria; Sandy petrofacies; Shoreline evolution; Spit; Tyrrhenian coast

Geothermal energy as a means to decarbonize the energy mix of megacities - Vargas, Carlos A.; Caracciolo, Luca; Ball, Philip J. (Communications Earth & Environment, 2022)
Geothermal energy can provide enough power to serve the current and future needs of megacities such as Bogota, Los Angeles and Jakarta and also provide flexibility and baseload capacity, according to an assessment of the geothermal resource base in each city.
CRIS-Team WoS Importer:2022-04-01

Holocene fluvial depositional regimes of the Huab River, Skeleton Coast, Namibia - Walsh, Ella; Caracciolo, Luca; Ravidà, Domenico; Burrough, Sallie; Thomas, David (Earth Surface Processes and Landforms, 2022)
Dryland fluvial systems respond to hydroclimate changes on Quaternary timescales, yet deciphering the palaeoenvironmental histories they preserve is often complex. Whilst hydrological signals are preserved in sediment stores as variations in sediment amount, character, and composition, studies in dryland settings such as Namibia that link sedimentological and compositional changes to palaeoflow are limited. Focusing on the Huab River, Skeleton Coast, this paper presents the first integrated study of textural, compositional, and stratigraphic features from a Namibian fluvial archive. Petrographic and heavy mineral assemblages from Raman laser spectroscopy are combined with lithostratigraphic and particle size analysis. Together with a chronology established through 42 optically stimulated luminescence ages, we reconstruct provenance, changes in river style, and fluvial response to climate. The Huab lithostratigraphic record details periods of flashy ephemeral flow interbedded with flow within well-defined channels. Compositional assemblages indicate that humid conditions during the early to mid-Holocene resulted in activation of sediment stores across the catchment. Episodic discharge within an ephemeral river from 12 to 9 ka was followed by a more sustained river flow in a channelized system from 7 to 5 ka. During the late Holocene, better hydraulic sorting, increased mechanical breakdown of polycrystalline grains, and flash flood lithofacies suggest that flow occurred within a more arid climate. This fine-scaled analysis of an ephemeral fluvial system indicates the utility of assessing compositional changes to distinguish between depositional regimes. This is an important approach for reconstructing fluvial response to climate and for obtaining palaeoenvironmental records from complex sedimentary archives in dryland river settings.
CRIS-Team Scopus Importer:2022-03-18
Keywords: facies analysis; heavy minerals; Holocene; Namibia; OSL dating; palaeoflow; petrography; Raman spectroscopy; sedimentary environment

Influence of granitoid textural parameters on sediment composition: Implications for sediment generation - Caracciolo, Luca; et al. (Sedimentary Geology, 2012)
Keywords: Composition; Glacial environment; Grain size; Mineral interfaces; Sediment generation; Textural parameters

Lithologic, geomorphic, and climatic controls on sand generation from volcanic rocks in the Sierra Nevada de Santa Marta massif (NE Colombia) - Hatzenbühler, Diana; Caracciolo, Luca; Weltje, G. J.; Piraquive, A.; Regelous, Marcel (Sedimentary Geology, 2022)
Tectonics, climate, and lithology are the three main factors controlling the generation and transfer of sediments as well as their textural and compositional signatures. In this paper, we investigate the generation of sands from volcanic rocks in nine drainages with mixed lithological assemblage in a high-relief – subtropical climate setting (Sierra Nevada de Santa Marta, NE Colombia). The integration of geomorphological analysis with sand petrography, and bulk-rock and clay geochemistry allows us to constrain the dynamics regulating the generation of sediments derived from felsic and mafic-intermediate volcanic basement rocks in relation to plutonic and metamorphic lithologies. The petrographic composition of modern fluvial sands from the area is extremely variable (litho-feldspatho-quartzose, feldspatho-quartzose, and quartzose-feldspatho-lithic), but it reveals a strong dilution of (especially mafic) volcanic compositional signals, and a consequent overrepresentation of plutonic and metamorphic lithologies. Traditional chemical weathering indices fail to represent the extent of chemical alteration, but instead seem to favour preservation of provenance signals. Chemical weathering primarily affects feldspars and the ferromagnesian groundmass of mafic volcanic rock fragments. Enrichment of ferromagnesian elements in the clay fraction supports the notion that mafic volcanic rock fragments are unstable relative to plutonic and metamorphic rocks. Drainage features (particularly river network and relief) control the abundance of volcanic lithic fragments and the rates and extent of chemical weathering. A linear log-ratio model permits us to quantify sediment generation from volcanic rocks in this mixed-lithology setting. The results indicate that even in the case where volcanic grains are practically absent in the sand fraction, there could still be up to 20% of volcanic rocks in the drainage basin, and in the case that 50% of the sand grains are volcanic, around 75% of drained lithologies are expected to be volcanic. Our results demonstrate that the contribution of volcanic detritus to modern sands systematically underrepresents the areal proportion of volcanics rocks in mixed source areas. Post-depositional diagenetic modifications are likely to alter and/or dissolve volcanic lithic fragments, making accurate reconstruction of sediment provenance even more difficult. Sediment-generation models based on a range of mixed lithologies in various tectonic and climatic settings will be needed to improve estimates of the abundance of volcanic rocks in drainage basins of ancient sediment routing systems.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Lithological; tectonic; and climatic controls; Quantitative provenance analysis; Sediment budget; Sediment generation; Weathering of volcanic rocks

Multidimensional Scaling of Varietal Data in Sedimentary Provenance Analysis - Vermeesch, P.; Lipp, A. G.; Hatzenbühler, D.; Caracciolo, Luca; Chew, D. (Journal of Geophysical Research F: Earth Surface, 2023)
Varietal studies of sedimentary provenance use the properties of individual minerals or mineral groups. These are recorded as lists of numerical tables that can be difficult to interpret. Multidimensional Scaling (MDS) is a popular multivariate ordination technique for analyzing other types of provenance data based on, for example, detrital geochronology or petrography. Applying MDS to varietal data would allow them to be treated on an equal footing with those other provenance proxies. MDS requires a method to quantify the dissimilarity between two samples. This paper introduces three ways to do so. The first method (“treatment-by-row”) turns lists of (compositional) data tables into lists of vectors, using principal component analysis. These lists of vectors can then be treated as “distributional” data and subjected to MDS analysis using dissimilarity measures such as the Kolmogorov-Smirnov statistic. The second method (“treatment-by-column”) turns lists of compositional data tables into multiple lists of vectors, each representing a single component of the varietal data. These multiple distributional data sets are subsequently subjected to Procrustes analysis or 3-way MDS. The third method uses the Wasserstein-2 distance to jointly compare the rows and columns of varietal data. This arguably makes the best use of the data but acts more like a “black box” than the other two methods. Applying the three methods to a detrital titanite data set from Colombia yields similar results. After converting varietal data to dissimilarity matrices, they can be combined with other types of provenance data, again using Procrustes analysis or 3-way MDS.
CRIS-Team Scopus Importer:2023-04-07
Keywords: apatite; provenance; sediment; statistics; titanite; zircon

Paleotectonics of a complex Miocene half graben formed above a detachment fault: The Diligencia basin, Orocopia Mountains, southern California - Caracciolo, Luca; et al. (Lithosphere, 2014)
These palinspastic restorations result in a coherent set of SW-NE-trending normal faults, basins (including Diligenica basin) and antiformal structures consistent with NW-SE-directed crustal extension from 24 to 18 Ma, likely resulting from the unstable configuration of the Mendocino triple junction.

PETROLOGICAL, GEOCHEMICAL, AND STATISTICAL ANALYSIS OF EOCENE-OLIGOCENE SANDSTONES OF THE WESTERN THRACE BASIN, GREECE AND BULGARIA - Caracciolo, Luca; et al. (Journal of Sedimentary Research, 2012)
The Rhodopian Orogen developed since the Late Cretaceous early Eocene during accretionary processes following the closure of the Vardar ocean basin, a branch of Neotethys. Through a multidisciplinary approach, including sandstone petrology and geochemistry of the clastic and volcanoclastic sediments, we reconstruct the unroofing history of the Rhodopian orogen and characterize the formation and the evolution of the western portions of the Thrace basin, in Greece and Bulgaria, between the late Eocene and Oligocene. Detrital modes of 127 sandstone samples provide evidence of three distinctive petrofacies: quartzolithic, quartzofeldspathic, and volcanoclastic. The petrographic composition gives evidence of contributions from three key source areas corresponding to the three main tectonic units: the Circum-Rhodope Belt, the Variegated Complex (ultramafic complex), and the Gneiss-Migmatite Complex. The three petrofacies reflect multiple provenance from different tectonic settings as they evolve from quartzolithic to quartzofeldspathic to volcanoclastic, corresponding to collisional orogen, crustal block uplift, and volcanic arc settings, respectively. Geochemical data on major elements and trace elements are used to discuss the efficacy of tectonic-setting discrimination diagrams and compare them to the Dickinson model as well as to distinguish and characterize (i) petrographically homogeneous gneiss-supplied subbasins and (ii) volcanic contributions to sandstone composition. Multivariate statistical techniques are used to unravel the complex web of factors controlling sediment composition. Biplot analysis highlights the influence of two independent processes: (1) mixing between carbonate and silicate phases, and (2) evolution from mafic to felsic source rocks. The latter indicates progressively increasing supply rates from deeper crustal levels. The compositional evolution of the sandstone suites of Thrace basin in NE Greece and SE Bulgaria is strictly related to various geodynamic stages of the Rhodope region. Provenance analysis of Thrace sandstones provide an example of the changing nature of orogenic belt sand associate basins through time, and may contribute to the general understanding of similar geodynamic settings.

Petrostratigraphic analysis of a Late Miocene mixed siliciclastic-carbonate depositional system (Calabria, Southern Italy): Implications for Mediterranean paleogeography - Caracciolo, Luca; et al. (Sedimentary Geology, 2013)
Keywords: Late Miocene; Mixed siliciclastic-carbonate sediments; Petrostratigraphy; Shallow water environments

Petrostratigraphic evolution of the Thrace Basin (Bulgaria, Greece, Turkey) within the context of Eocene-Oligocene post-collisional evolution of the Vardar-Izmir-Ankara suture zone - Caracciolo, Luca; et al. (Geodinamica Acta, 2013)
Eocene-Oligocene paleogeographic/paleotectonic reconstructions of the Rhodopian - northern Aegean - western Black Sea region largely ignore the Thrace Basin, a large sedimentary basin up to 9 km thick that has been long interpreted as a forearc basin developed in a context of northward subduction. Recent structural, stratigraphic, petrologic, and sedimentologic data challenge this notion and may instead be interpreted within a context of upper-plate extension during the complex transition between the collisional tectonic regime related to the closure of Vardar-Izmir-Ankara oceanic realm and the extensional regime characterizing the Oligocene-Neogene evolution of the Aegean and peri-Aegean regions. The detritus filling the Thrace Basin was derived from two main sediment source areas: (i) the mostly metamorphic terrains of the Rhodopes to the west and (ii) the Vardar-Izmir-Ankara and Biga (intra-Pontide?) subduction-accretion prisms to the southwest. During most of the Eocene-Oligocene, the entire basin was characterized by a complex physiography, as shown by commercial seismic lines in the subsurface and abrupt lateral facies change at the surface. Such physiography was controlled by a series of basement highs trending from WNW-ESE (in the eastern and northern portions of the basin) to WSW-ENE (in the western and southern portions of the basin) which influenced sediment dispersal and the areal distribution of paleoenvironments.
Keywords: post-orogenic collapse; upper plate extension; sandstone detrital modes

Provenance of Tertiary volcanoclastic sediment in NW Thrace (Bulgaria): Evidence from detrital amphibole and pyroxene geochemistry - Caracciolo, Luca; et al. (Sedimentary Geology, 2016)
Detrital heavy mineral and bulk rock geochemistry and a review of sandstone petrographic data have been used to investigate the post-collisional effusive magmatism that followed the closure of the Vardar Ocean and the generation of volcanic sediments in a complex and compositionally variable volcanic region. Available petrographic data gives evidence of contributions from three key source areas corresponding to the three main tectonic units: the structurally lower Gneiss-Migmatite Complex (Byala Reka-Kechros and Kesebir-Kardamos domes) and the upper Variegated (Kimi) Complex, both fringed by the low-to-medium-grade Mesozoic rocks of the Circum-Rhodope Belt. Besides the deposition of siliciclastic material, volcanic contributions from both, intermediate and acid products represent an important source of sediment in the area. Despite dominant intermediate to acid volcanic products, volcanic lithic fragments in sandstones (microlithic, lathwork and brown vitric textures) indicate main inputs from intermediate and basic-intermediate products generating questions on the interpretation of volcanic detritus in reconstruction of provenance. Detrital amphibole and pyroxene chemistry is used to characterise the supply of volcanic material as well as the dispersal mechanisms and understand the role played by each of the volcanic centers present in the area in the infill of the north-western Thrace basin. Amphibole chemistry reveals high compositional heterogeneity according to both compositional variability of the numerous volcanic centres active at the time of deposition and presence of metamorphic amphibole. Al-4 and Al-T apfu values indicate that most of the amphiboles from the NERZ are not of volcanic origin and their presence can only be attributed to the numerous amphibolite facies metamorphic rocks abundantly documented in the area. Detrital amphibole compositions from the ZKVS indicate major contributions from the Iran Tepe and Zvedzel volcanoes. Analysed detrital clinopyroxenes from the NERZ are mostly diopside-augite, with no hedenbergite or Fe-augite detected. The Al-4/Al-6 ratio is comparable with compositions of volcanic pyroxenes from the Momchilgrad-Arda (ZKVS) region and products from the pre-caldera phase of the Borovitza. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Single grain geochemistry; Provenance analysis; Thrace Basin; Rhodope; Volcaniclastic sedimentation; Eastem Mediterranean basin

Quantitative analysis of crystal-interface frequencies in granitoids: Implications for modelling of parent-rock texture and its influence on the properties of plutoniclastic sands - Weltje, Gert Jan; Paredis, Bram; Caracciolo, Luca; Heins, William (Sedimentary Geology, 2018)
Generation of sediments from crystalline rocks is the result of a complex and incompletely understood suite of processes. The time evolution of the rock-fragment assemblage in sands derived from granitoids is determined by the relative strengths of crystal interfaces and their abundances in the parent rock. In this study we highlight the role of crystal-interface frequencies in granitoids. Strong evidence for non-random texture with significant implications for predicted interface frequencies have been reported in previous studies. We analysed available interface-frequency data from granitoids using methods of compositional data analysis, and connected our results to existing texture classifications. On average, granitoids display a high degree of ordering with significant depletion of isomineralic interfaces relative to expectations based on random texture. Analysis of 210 normalized interface frequency distributions from nine different granitoids reveals a consistent pattern of variation among interface frequencies, which suggests a single underlying petrogenetic process related to the combined effects of nucleation and textural equilibration ("coarsening").In view of the large scatter of relative interface frequencies within and among granitoids, we propose to model their distribution empirically for the purpose of calibrating sediment-generation studies. Multivariate normal distributions of centred log-ratio transformed relative frequencies are capable of capturing ∼95% of the observed variability with a limited number of dimensions. As a rule of thumb, the number of dimensions needed to approximate interface-frequency counts can be taken equal to the number of mineral classes, which is (much) smaller than the number of interface classes. Mathematical analysis shows that the joint variability of rock texture and composition may be factorized into three statistically independent measures: modal composition, crystal-size probability density functions, and normalized interface frequencies. The potential independence of these measures permits objective identification of petrogenetically significant correlations among them, which will be indicated by statistically significant cross-covariances. At this stage, inferences from microscopic texture analysis cannot be extrapolated to the scale of entire drainage basins in which sediments are generated, because insufficient data are available on the large-scale spatial heterogeneity of texture and composition of granitoid parent rocks<br

Reconstructing environmental signals across the Permian-Triassic boundary in the SE Germanic Basin: A Quantitative Provenance Analysis (QPA) approach - Caracciolo, Luca; Ravidà, Domenico; Chew, David; Janßen, Meike; Luensdorf, Keno Nils; Heins, William A.; Stephan, Tobias; Stollhofen, Harald (Global and Planetary Change, 2021)
Global tectonic and climatic models for the Permian-Triassic boundary (PTB) are highly debated. One of the most disputed topics is the temperature increase associated with CO2 emissions generated by the Siberian Trap volcanism and its potential influence on chemical weathering and associated variations in sediment fluxes. By integrating crustal architecture, plate modelling, structural kinematics, and two climatic models, we reconstruct the drainage evolution of Variscan tectonostratigraphic units from the SE portion of the Germanic Basin, from which we also extract the parameters necessary to calculate sediment flux across a time-scale of 28 Ma (Guadalupian-Lower Triassic). We reconstruct the sedimentary response to climatic and tectonic perturbations using Quantitative Provenance Analysis (QPA) and integrate compositional data into a sedimentological framework, paleodrainage and paleoclimatic models. Raman heavy mineral analysis, as well as geochronology and geochemistry of detrital apatite, zircon, and rutile, document variation in drainage lithologies and sediment flux which are controlled by regional extensional tectonics and increasingly humid conditions at the PTB. The sedimentary successions of the SE Germanic Basin record climatic perturbations on a 104 years timescale, while the effects of tectonics are visible on a 106 years timescale. The interplay of climate, tectonics and lithology, and their effects on sediment production and drainage evolution resulted in changes in sediment flux from 2.3 Mt./yr during the Guadalupian (Capitanian), to 3.80 Mt./yr in the Lopingian (Changhsingian) to 7.44 Mt./yr at the end of the Lower Triassic (Olenekian). The multifaceted workflow provided in this study represents the first step towards more precise reconstructions of sediment routing systems in deep-time and provides the first ground-truthed quantification of sediment flux across the Permian-Triassic Boundary.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Tectonic and climatic perturbations; Environmental signals; External forcing controls; Quantitative Provenance Analysis; Permian-Triassic Boundary

Reconstructing environmental signals across the Permian-Triassic boundary in the SE Germanic basin: Paleodrainage modelling and quantification of sediment flux - Ravidà, Domenico; Caracciolo, Luca; Heins, William A.; Stollhofen, Harald (Global and Planetary Change, 2021)
Reconstructing sediment load in deep-time is one of the greatest challenges in the reconstruction of ancient sediment routing systems, particularly because solid statistical models are absent and paleo-climatic, paleo-tectonic, and sedimentary constraints are lacking. This study proposes a reliable workflow for the estimation of paleo-sediment fluxes (Qs) applying the BQART model to a case study from the SE Germanic Basin across the Middle Permian – Early Triassic interval. The input parameters of the simulations derive from: integrated plate modelling and structural kinematics; paleodrainage and paleogeographic reconstructions; global circulation models; and sandstone compositional signatures. We apply Monte Carlo simulation to overcome the input uncertainties for eight different scenarios obtained from the combination of two area estimates, two climate models, and two time resolutions. All the models are in general agreement and show changes in sediment flux (i) being steady or declining slightly through the Middle Permian, (ii) an increase of 31% at the beginning of the Late Permian (3.6–4.6 Mt yr−1), (iii) and a nearly 100% rise at the onset of the Early Triassic (7.4 Mt yr−1). The variation of sediment load across the PTB is coeval to the transition from meandering/sabkha to perennial braided depositional settings recorded from the well data of Obernsees-1 and Lindau-1; it results from both increased tectonism and seasonal precipitation. The Qs estimates agree with those of modern drainages under analogous environmental conditions, highlighting the reliability of the workflow included in this study for the quantification of sediment flux in deep time. Furthermore, the results of this study provide new insights on the highly debated evolution of the continental sequences across the PTB with strong implications for both past and future paleo-environmental reconstructions.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Central European Basin Systems; External forcing controls; Paleodrainage reconstruction; Permo-Triassic boundary; Sediment flux; Sediment routing system

Reply to the Discussion by Maravelis and Zelilidis on "Unravelling provenance from Eocene-Oligocene sandstones of the Thrace Basin, North-east Greece" by Caracciolo etal. (2011), Sedimentology, 58, 1988-2011. - Caracciolo, Luca; et al. (Sedimentology, 2013)
Keywords: Compositional signatures; Limnos Island; NAegean evolution; provenance; Thrace basin

Sandstone petrology and mudstone geochemistry of the Peruc-Korycany Formation (Bohemian Cretaceous Basin, Czech Republic) - Caracciolo, Luca; et al. (International Geology Review, 2011)
We have studied the petrography and the bulk-rock geochemistry of arenites and mudstones of the Cenomanian Peruc-Korycany Formation to characterize their provenance and sedimentary history, as well as the influence of weathering, hydraulic sorting, and recycling of the source rocks. The Peruc-Korycany Formation contains sedimentary facies reflecting both meandering- and braided-river systems and shallow-marine systems. Differences in the three depositional settings did not cause distinctly different modifications of the framework compositions of the arenites. The sand from the fluvial systems is very mature (Qm98F0Lt2). These fluvial arenites were subsequently modified by shallow-marine processes; reworking produced very slight decreases in the abundance of lithic fragments and polycrystalline quartz grains. The Cenomanian strata of the Bohemian Cretaceous Basin were derived dominantly from metasedimentary and crystalline rocks of the Palaeozoic Tepla-Barrandian and Cadomian Moldanubian units, respectively. Periods of low tectonic activity resulted in the deposition of arenites with quartzose framework compositions, indicating that climatic and/or transport/depositional-environmental controls overwhelmed factors such as source-rock compositions. Ultrastable dense minerals are useful indicators of sedimentary recycling within the Peruc-Korycanytarenites. Mudstone samples are characterized by abundant kaolinite, illite, chlorite, and quartz but by negligible amounts of goethite and gypsum. Concentrations normalized to the post-Archaean Australian shale (PAAS) show that the sediments are strongly depleted of Na, K, Ca, Sr, and Ba, probably because of the mobility of these elements during weathering. Chemical indices of alteration (CIA, CIW, and PIA) show that the degree of weathering of the source area was high. The data fall closer to the compositional fields of highly weathered minerals such as kaolinite, gibbsite, and chlorite on an A-CN-K diagram. The indices of compositional variability of the studied samples are much less than 1, suggesting that the samples are compositionally mature and were likely dominated by recycling. The elemental ratios critical of provenance (La/Sc, Th/Sc, Th/Co, Th/Cr, and Cr/Th) are similar to fine fractions derived from the weathering of mostly granitoids rather than mafic rocks.
Keywords: Bohemian Cretaceous Basin; mudstone; provenance; quartzarenite; sedimentary recycling

Sedimentary and thermal evolution of the Eocene-Oligocene mudrocks from the southwestern Thrace Basin (NE Greece) - Caracciolo, Luca; et al. (Basin Research, 2016)

Sedimentary facies analysis of the Mesozoic clastic rocks in southern Peru (Tacna, 18°S): Towards a paleoenvironmental Re-definition and stratigraphic Re-organization - Alvan, Aldo; Jacay, Javier; Caracciolo, Luca; Sanchez, Elvis; Trinidad, Ines (Journal of South American Earth Sciences, 2018)
The Mesozoic rocks of southern Peru comprise a Middle Jurassic to Early Cretaceous sedimentary sequence deposited during a time interval of approximately 34 Myr. These rocks constitute the Yura Group (Callovian to Tithonian) and the Hualhuani Formation (Berriasian). Basing on robust interpretation of facies and petrographic analysis, we reconstruct the depositional settings of such units and provide a refined stratigraphic framework. Accordingly, nine types of sedimentary facies and six architectural elements are defined. They preserve the record of a progradational fluvial system, in which two types of fluvial systems regulated the dispersion of sediments: (i) a high-to moderate-sinuosity meandering system (Yura Group), and a later (ii) incipient braided system (Hualhuani Formation). The Yura Group (Callovian-Tithonian) represents the onset of floodplain deposits and lateral accretion of point-bar deposits sited on a semi-flat topography. Nonetheless, the progradational sequence was affected by at least two rapid marine ingressions occurred during Middle Callovian and Tithonian times. Such marine ingressions reveal the proximity of a shallow marine setting. In response to increase in topographic gradient, the Hualhuani Formation (Berriasian) deposited as extensive multistory sandy channels. The mineralogy of the Mesozoic sediments suggests sediment supplies and recycling from a craton interior (i.e. Amazon Craton and/or plutonic sources) located eastward of the study are
Keywords: Yura groupMesozoic Arequipa basinCentral AndesFacies analysis

Sediment generation and provenance: Processes and pathways - Caracciolo, Luca; et al. (Sedimentary Geology, 2016)

Sediment Generation and Sediment Routing Systems - Caracciolo, Luca; Chew, David; Andò, Sergio (Earth-Science Reviews, 2020)

Sediment generation and sediment routing systems - Caracciolo, Luca; Chew, David; Andò, Sergio (Elsevier, 2021)

Sediment generation and sediment routing systems from a quantitative provenance analysis perspective: Review, application and future development - Caracciolo, Luca (Earth-Science Reviews, 2020)
Sediment Routing Systems (SRS) and Sediment Generation (SG) are two branches of sedimentary geology which are complementary, although their full integration remains incomplete. SRS connect all the steps of the journey of sediments from their formation to final deposition in relation to the denudation of sediment sources, the transfer of erosional products and their final deposition. SG is a branch of provenance analysis focussing on the quantification of the processes governing the production (Qs) and dispersal of sediments from known parent rocks, and the prediction of the amount and compositional-textural properties of sediments produced under given tectonic and climatic settings. The integration of the two disciplines is fundamental to tackle some of the open problems in sedimentary geology, including (i) the dynamics regulating the generation and release of sediments from upstream catchments to the floodplains, (ii) particle trajectories, (iii) residence time and mineralogical modifications in temporary storage environments (iv) sediment selective extraction and (v) the shredding of environmental signal propagation in both (vi) actualistic and deep-time SRS. I introduce all the elements which are necessary to both disciplines, with particular emphasis on quantitative provenance analysis (QPA). The SG approach is required to quantify lithological controls on Qs, and include it into the stream power law. QPA and the ‘Provenance Toolbox’ provide the compositional framework which is necessary for the characterisation of the erosional products. Both the advantages and limitations of each analytical tool are explored, and best practices for successful analytical workflows are discussed in light of a full integration into SRS research.<br

Sediment generation in humid Mediterranean setting: Grain-size and source-rock control on sediment geochemistry and mineralogy (Sila Massif, Calabria) - Caracciolo, Luca; et al. (Sedimentary Geology, 2016)
Grain-size control on sediment composition is investigated in modern proximal sediment from the Sila Massif, where basic to felsic intrusive rocks are exposed in a Mediterranean humid-temperate upland climate. Samples were taken from small creeks and weathering profiles from three areas reflecting different bed rock compositions. Samples were separated into eleven grain size fractions from very coarse sand to clay and analyzed by (i) X-ray fluorescence for chemical composition and (ii) X-ray diffraction and Mineral Liberation Analysis for mineralogical composition. The chemical composition vs. grain size relations were modeled by compositional linear regression. Mineralogical composition of selected samples is used to substantiate the interpretations based on geochemistry. Results: reveal a high degree of chemical weathering with chemical index of alteration (CIA) up to 92. High CIA values are restricted to the fine-grained fractions, while sand-sized sediment average at low to moderate CIA values (similar to 60). Although strongly weathered, the three sample suites reflecting basic to felsic plutonic bed rock can be effectively discriminated across all grain-size classes using trace elements such as V, Rb, and Sr. Linear trend modeling and mineralogical data reflect similar patterns for all sample suites implying similar processes independent of source rock composition. This includes overall decrease of quartz and K-feldspar over the full grain-size range from very coarse sand to clay, which is contrasted by overall increase of sheet silicates from coarse to fine. Among the latter, increase of clay minerals strongly outpaces the increase of micas in silt to clay fractions. A more complex behavior is shown by plagioclase, which is most abundant in intermediate grain-size fractions for all sample suites. This is likely caused by initial hydrolysis along cleavage and twinning planes and subsequent breakage of plagioclase crystals into smaller fragments. Towards finer grain size, intense hydrolysis has destroyed most feldspars. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Geochemistry; Mineralogy; Chemical weathering; Comminution; Provenance; Compositional linear regression

Sedimentología para la transición energética: proyecto SOSGAS, un ejemplo de flujo de trabajo para la evaluación de calidad de reservorios - Viseras, César; Cabello, Patricia; Yeste, Luis M.; Alcalde, Juan; López-Blanco, Miguel; Cuevas, José L.; Gil-Ortiz, Marc; Caracciolo, Luca; De Mesquita Veloso, Fernanda; Heinemann, Niklas; Falivene, Oriol; Varela, Augusto N.; et al. (Geogaceta, 2024)
The research workflow developed in the SOSGAS project is presented, aimed at the Quality Assessment as a reservoir of CO2 and green H2 of heterogeneous Mesozoic and Cenozoic fluvial and deltaic formations of the Iberian Meseta and the Ebro and Graus-Tremp Basins. Through the integrated study of outcrop and subsurface data (derived from boreholes drilled behind the outcrops), conceptual models are developed for each examined case, describing variations in sedimentary heterogeneities. These models contribute to the static modelling of different geobodies and their petrophysical properties. Finally, dynamic modelling, based on gas injection simulation experiments (CO2 and H2) into static models, enables the analysis of the sustainability of geo-storage projects for these key fluids in the energy transition.
CRIS-Team Scopus Importer:2025-02-04
Keywords: CO; energy transition; geo-storage; green H; sedimentology

Sourcing the sand: Accessory mineral fertility, analytical and other biases in detrital U-Pb provenance analysis - Chew, David; O'Sullivan, Gary; Caracciolo, Luca; Mark, Chris; Tyrrell, Shane (Earth-Science Reviews, 2020)
Interpreting the wealth of new data derived from the diverse suite of modern single-grain provenance approaches available to a sedimentologist requires a thorough understanding of the potential biases in the information recorded by each mineral-provenance system. This review focuses on the various possible mineral-specific biases in U-Pb accessory mineral provenance studies employing the minerals zircon, rutile, apatite, monazite and titanite, focussing on biases resulting from variations in source-rock mineralogy (fertility). Fertility is intimately linked to the mineral petrogenesis of crystalline basement sources, which is another key aspect of this review. This petrogenetic information, which often resides in the specialist petrology literature, has great relevance to fertility studies (particularly those measuring mineral content in modern river sediment using confluence and along-trunk sampling) as trace-element abundances and/or elemental ratios in many accessory minerals can be linked to specific lithologies. Other mineral-specific biases in single-grain provenance analysis considered include physical and chemical modifications both before and after deposition, while the diverse suite of modern single-grain analytical approaches also requires understanding of potential methodological and laboratory induced-biases. A series of multi-proxy provenance studies are presented where fertility bias apparently plays a significant role. In magma-poor metamorphic belts (e.g. segments of the Himalayas and Caledonides-Appalachians), it is shown that zircon growth is limited, and monazite, apatite or rutile associated with the youngest tectonomagmatic events are significantly more fertile. Such multi-proxy provenance studies will be greatly aided in the future by high-throughput, coupled U-Pb age – trace-element analyses integrated with automated heavy mineral determinations employing highly efficient sample preparation protocol

Sourcing the sand: Accessory mineral fertility, analytical and other biases in detrital U-Pb provenance analysis - Chew, David; O'Sullivan, Gary; Caracciolo, Luca; Mark, Chris; Tyrrell, Shane (Earth-Science Reviews, 2020)
Interpreting the wealth of new data derived from the diverse suite of modern single-grain provenance approaches available to a sedimentologist requires a thorough understanding of the potential biases in the information recorded by each mineral-provenance system. This review focuses on the various possible mineral-specific biases in U-Pb accessory mineral provenance studies employing the minerals zircon, rutile, apatite, monazite and titanite, focussing on biases resulting from variations in source-rock mineralogy (fertility). Fertility is intimately linked to the mineral petrogenesis of crystalline basement sources, which is another key aspect of this review. This petrogenetic information, which often resides in the specialist petrology literature, has great relevance to fertility studies (particularly those measuring mineral content in modern river sediment using confluence and along-trunk sampling) as trace-element abundances and/or elemental ratios in many accessory minerals can be linked to specific lithologies. Other mineral-specific biases in single-grain provenance analysis considered include physical and chemical modifications both before and after deposition, while the diverse suite of modern single-grain analytical approaches also requires understanding of potential methodological and laboratory induced-biases. A series of multi-proxy provenance studies are presented where fertility bias apparently plays a significant role. In magma-poor metamorphic belts (e.g. segments of the Himalayas and Caledonides-Appalachians), it is shown that zircon growth is limited, and monazite, apatite or rutile associated with the youngest tectonomagmatic events are significantly more fertile. Such multi-proxy provenance studies will be greatly aided in the future by high-throughput, coupled U-Pb age – trace-element analyses integrated with automated heavy mineral determinations employing highly efficient sample preparation protocols.
CRIS-Team Scopus Importer:2020-02-04

The diagenetic destruction of porosity in plutoniclastic petrofacies: The Miocene Diligencia and Eocene Maniobra formations, Orocopia Mountains, southern California, USA - Caracciolo, Luca; et al. (Geological Society of London, 2014)

The impact of Etendeka flood basalts on the diagenesis of the fluvio-aeolian Jurassic Etjo Formation, Namibia - Salomon, Eric; Caracciolo, Luca; Stollhofen, Harald; Bonnell, Linda; Lander, Robert H.; Kittel, Mario (The impacts of volcanism on sedimentary basins and their energy resources, 2022)
The rapid effusion of volcanic rocks of large igneous provinces results in a relatively rapid burial of underlying rocks. In such settings, siliciclastic deposits and potential reservoir rock may on the one hand experience a high degree of mechanical compaction prior to the onset of significant chemical compaction, while on the other hand an increased geothermal gradient or hydrothermal activity may speed up cementation processes. To assess such impact, we present the results of a study on the diagenesis of the aeolian upper unit of the Jurassic Etjo Formation in Namibia, that was subject to burial related to the emplacement of the voluminous Lower Cretaceous Etendeka flood basalts that reached presumed thicknesses of up to c. 2-5 km, and is today again exposed at the Earth’s surface. We have studied the Etjo Formation at three key localities, namely Waterberg, Mt. Etjo, and Gamsberg, that lie >100 km apart from each other. At all locations, the sandstone is texturally mature and quartzose with very low quantities of feldspars and lithic grains. However, petrographic analysis shows that the Etjo Formation has experienced a very different diagenesis at each location with respect to intergranular volume (IGV) and quartz cementation (Fig. 1). Average IGV and quartz cement values are 23.7 % and 6.5 % (Waterberg), 19.7 % and 15.4 % (Mt. Etjo), and 30.7 % and 24.3 % (Gamsberg). Porosity values, based on buoyancy measurements, are on average 21.0 w.t.% (Waterberg), 8.1 w.t.% (Mt. Etjo), and 5.2 w.t.% (Gamsberg). Also permeability, based on air permeameter measurements, varies between the locations with highest values at Waterberg (15 – 2819 mD), intermediate values at Mt. Etjo (14 – 132 mD), and lowest values at Gamsberg (2 – 82 mD). We attribute the differences of IGV and quartz cement to spatial thickness variations of the overlying volcanic rock column. Higher compaction and cementation values at Mt. Etjo compared to Waterberg are likely related to the proximity of Mt. Etjo to the presumed center of Etendeka volcanism. Gamsberg is the only location where a first generation of quartz overgrowth formed prior to Etendeka burial, as evidenced by cathodoluminescence imagery, which likely has stabilized the grain framework to prevent further mechanical compaction during this burial. These interpretations are supported by TouchstoneTM numerical modeling for sandstone diagenesis. Permeability appears to be linked to the summed up quantity of quartz cement and eogenetic infiltrated clay. Our study demonstrates the variability in diagenetic properties that a sandstone formation can attain depending on its location under a massive sheet of flood volcanic rocks. <br

The Rhodope Zone as a primary sediment source of the southern Thrace basin (NE Greece and NW Turkey): evidence from detrital heavy minerals and implications for central-eastern Mediterranean palaeogeography - Caracciolo, Luca; et al. (International Journal of Earth Sciences, 2015)
Keywords: Biga Peninsula; Circum-Rhodope Belt; Cr-spinel geochemistry; Detrital heavy minerals; Sediment provenance; Thrace basin

The role of diagenesis and depositional facies on pore system evolution in a Triassic outcrop analogue (SE Spain) - Caracciolo, Luca; et al. (Marine and Petroleum Geology, 2014)
Keywords: Diagenesis; Fluvial facies; Outcrop analogue; Pore system; TAGI; Triassic

Tidal versus fluvial point bars: Key features from the integration of outcrop, core and wireline log information of Triassic examples - Yeste, Luis Miguel; Gil-Ortiz, Marc; García-García, Fernando; Viseras, César; Mcdougall, Neil David; Cabello, Patricia; Caracciolo, Luca (Depositional Record, 2024)
The Triassic red beds of the Tabular Cover of the Iberian Meseta are an excellent reservoir outcrop analogue, a direct consequence of high-quality exposures, which offer exceptional three-dimensional outcrops, as well as a wide variability of depositional environments. Fluvial and transitional with tide-influenced and wave-influenced settings are recognised. Three point bar geobodies of similar scale, but influenced by different processes, were selected from this succession. Point bar geobody 1 was influenced by purely fluvial processes while geobodies 2 and 3 were tide-influenced. Both types of geobody were developed as point bar deposits in sinuous channels. A fully integrated study was carried out on these geobodies, utilising both outcrop and subsurface-based approaches, to characterise the key differences between fluvial and tidal point bars in the sedimentary record. The outcrop-based component involved traditional field data collection methods alongside digital techniques and data capture, including the use of digital outcrop models. Additionally, subsurface-based methods were employed, utilising core and wireline logs obtained from wells drilled in close proximity to the outcrop. The integration of these approaches aims to accurately differentiate the depositional settings of the three different geobodies, which while apparently very similar in many key respects also exhibit considerable differences when considered from the perspective of subsurface management of potentially similar geobodies. This study also emphasises the need to clearly distinguish high-sinuosity deposits based on their depositional sub-environment in order to properly evaluate their potential for subsurface management. Additionally, it highlights the presence and importance of internal baffles that may well influence fluid migration and indeed even compartmentalise geobodies. Three point bar geobodies of similar scale, but influenced by different processes, have been selected in this succession. A fully integrated study was carried out on these geobodies, utilising both outcrop-based and subsurface-based approaches, to characterise the key differences between fluvial and tidal point bars in the sedimentary record.
CRIS-Team Scopus Importer:2024-05-24
Keywords: fluvial point bar; outcrop analogue; outcrop/behind-outcrop characterisation; TIBEM; tidal point bar; Triassic

Towards an improved discrimination and correlation of Permian-Lower Triassic sediments in Central Europe: A chemostratigraphic approach - Ravidà, Domenico; Caracciolo, Luca; Heins, William A.; Stollhofen, Harald (Sedimentary Geology, 2023)
The stratigraphic classification and correlation of Permian-Lower Triassic clastic beds in the Central European Basin System traditionally rely on geophysical, bio-, and lithostratigraphic methods. However, in basin margin areas, the accuracy of these tools is diminished due to the heterogeneous distribution of stratigraphic markers, lack of index fossils, and greater climatic and tectonic disturbance. To overcome these limitations, this study introduces a more versatile, multifaceted and chemostratigraphy-based approach. By integrating results from bulk X-ray fluorescence analysis, sandstone petrography, Raman heavy mineral analysis, lithofacies characterisation and borehole gamma-ray logs, we produce robust multi-stratigraphic schemes for selected sequences in the Franconian Basin (SE Central European Basin System). Hierarchical chemostratigraphic zones, comprising five chemozones and sixteen subzones, were designed using key elemental ratios (Ga/Rb, Rb/K, Na/K, Ca/Mg, Cr/Ti, Th/Ti, Nb/Th, Ti/Nb, P/Ti, Zr/P, Zr/Y), whose changes through time reflect modifications in the mineralogical composition of sedimentary rocks. To ensure precise interpretations of geochemical data, we established links between mineralogical and chemical components through statistical processing and direct comparison with mineralogical assemblages. Our results demonstrate that chemostratigraphic boundaries can identify major changes in palaeo-depositional environments and sediment sources induced by eustatic, tectonic and climatic disturbances. For example, changes in the P/Ti and Zr/P ratios across the CP3-CT1 document the increased abundance in apatite-rich granitic detritus, resulting from the exposure of new source lithologies in the catchment area due to Early Triassic synsedimentary tectonism. Since these perturbations had a regional impact on sedimentation, their geochemical fingerprints are correlated across the basin, regardless of lithofacies variability or distance between sections. Moreover, integrating characteristic geochemical signals into multi-stratigraphic schemes enables more precise placement of stratigraphic boundaries, identification of locally deposited/preserved stratigraphic markers, and overall refinement of outdated classification schemes. The chemostratigraphic approach introduced in this study offers a solution to the limitations of conventional stratigraphic tools, allowing robust characterisations and correlations of Permian-Triassic sequences in the marginal regions of the Central European Basin System. In addition, the multi-analytical workflow for processing geochemical data, refining stratigraphic schemes and attributing geochemical anomalies to environmental perturbations represents a further step towards more precise applications of chemostratigraphy to the depositional record.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Basin-scale correlation; Central European Basin System; Chemostratigraphy; Clastic sediments; External forcing controls; Permo-Triassic boundary

Understanding sedimentary processes in the uphill catchment of Source-to Sink-Systems: An example from the Sierra Nevada de Santa Marta (NE Colombia) - Caracciolo, Luca; Hatzenbühler, Diana; Chew, D.; Weltje, G. J.; Liedel, Stefan; Vermeesch, P.; Piraquive, A.; Regelous, Marcel; Lünsdorf, K.; Villamizar-Escalante, N. (Earth-Science Reviews, 2025)
The character of sediments generated in the uphill catchments is markedly variable and exert a primary control on the sediment cascade and the evolution of source-to-sink systems. Understanding these processes is therefore critical to better understand how these systems function in both modern and deep-time settigns. This study aims to understand and quantify the processes regulating sediment generation and transfert in the uphill catchments of the Sierra Nevada de Santa Marta (SNSM) - the world's highest coastal range within subtropical regions. We tackle the complex task of quantify the role of external forcings on sediment production in 17 drainages basins within the SNSM by challenging conventional assumptions and introducing new compositional models. Our research significantly expands the existing knowledge base on compositional modelling by presenting a systematic framework for characterizing sediment generation, particularly focusing on the influence of tectonics, climate, lithological factors, and analytical reliability. We produced a robust compositional database encompassing optical petrography (11,463 grains), Raman heavy mineral analysis (44,782 grains), detrital geochronology (apatite, titanite, and zircon – 6378 grains), apatite (1159 grains) and titanite (1571 grains) geochemistry, and bulk-rock and silt-clay geochemistry.We present a novel linear log-ratio (end-member) sediment generation model calibrated on geomorphological parameters as connectivity and erodibility, facilitating the evaluation of sediment generation capacities from metamorphic, plutonic, and volcanic lithologies. Sediment texture and composition vary remarkably from drainage to drainage, providing the elements to model both the relative (by comparing lithologies) and absolute capacity of drainage lithologies to produce sediments, in the settings of the SNSM. Our results reveal significant variations in sediment texture and composition among drainages, providing insights into both the relative and absolute capacity of different lithologies to produce sediments in the SNSM setting. We found that metamorphic rocks produce higher amounts of sand compared to plutonic and volcanic lithologies, while the sediment generation capacity of plutonic rocks is up to 9 times higher than that of volcanic lithologies. In mixed drainages with equal proportions of metamorphic and other rocks, metamorphic detritus can constitute up to 60 % of sand compositions. Surprisingly, geomorphological parameters like structural connectivity and erodibility played a minor role in sediment generation in this tectonic setting, contrary to findings in other regions. This study underscores the importance of understanding processes operating in uphill catchments to better constrain those acting in other sectors of Source-to-Sink systems. Our findings contribute to advancing quantitative methods in provenance analysis and improve our understanding of sediment generation and routing in complex tectonic and climatic settings.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Compositional data analysis; Quantitative provenance analysis; Sediment budget; Sediment generation models; Source to sink systems

Unravelling provenance from Eocene-Oligocene sandstones of the Thrace Basin, North-east Greece - Caracciolo, Luca; et al. (Sedimentology, 2011)
New sandstone petrology and petrostratigraphy provide insights on Palaeogene (Middle Eocene to Oligocene) clastics of the Thrace Basin in Greece, which developed synchronously with post-Cretaceous collision and subsequent Tertiary extension. Sandstone petrofacies are used as a tool to unravel complex geodynamic changes that occurred at the southern continental margin of the European plate, identifying detrital signals of the accretionary processes of the Rhodope orogen, as well as subsequent partitioning related to extension of the Rhodope area, followed by Oligocene to present Aegean extension and wide magmatic activity starting during the Early Oligocene. Sandstone detrital modes include three distinctive petrofacies: quartzolithic, quartzofeldspathic and feldspatholithic. Major contributions are from metamorphic basement units, represented mostly by low to medium-grade lithic fragments for the quartzolithic petrofacies and high-grade metamorphic rock fragments for the quartzofeldspathic petrofacies. Volcaniclastic sandstones were derived from different volcanic areas, with a composition varying from dominantly silicic to subordinate intermediate products (mainly rhyolitic glass, spherulites and felsitic lithics). Evolution of detrital modes documents contributions from three key source areas corresponding to the two main crystalline tectonic units: (i) the Variegated Complex (ultramafic complex), in the initial stage of accretion (quartzolithic petrofacies); (ii) the Gneiss-Migmatite Complex (quartzofeldspathic petrofacies); and (iii) the Circum-Rhodope Belt. The volcaniclastic petrofacies is interbedded with quartzofeldspathic petrofacies, reflecting superposition of active volcanic activity on regional erosion. The three key petrofacies reflect complex provenance from different tectonic settings, from collisional orogenic terranes to local basement uplift and volcanic activity. The composition and stratigraphic relations of sandstones derived from erosion of the Rhodope orogenic belt and superposed magmatism after the extensional phase in northern Greece provide constraints for palaeogeographic and palaeotectonic models of the Eocene to Oligocene western portions of the Thrace Basin. Clastic detritus in the following sedimentary assemblages was derived mainly from provenance terranes of the Palaeozoic section within the strongly deformed Rhodope Massif of northern Greece and south-east Bulgaria, from the epimetamorphic units of the Circum-Rhodope Belt and from superposed Late Eocene to Early Oligocene magmatism related to orogenic collapse of the Rhodope orogen. The sedimentary provenance of the Rhodope Palaeogene sandstones documents the changing nature of this orogenic belt through time, and may contribute to a general understanding of similar geodynamic settings.
Keywords: Eocene-Oligocene; magmatism; North-east Greece; Rhodope Massif; sandstone detrital modes; Thrace Basin

Unveiling coastal dynamics: Investigating beach sediment distribution patterns along the Lithuanian Baltic Sea coast through heavy mineral analysis - Karlonienė, Dovilė; Caracciolo, Luca; Pupienis, Donatas (Marine Geology, 2024)
Effective coastal management requires an understanding of sediment dynamics. This study examines the distribution of heavy minerals (HMs) in two distinct coastal regions: the mainland and spit, each with unique sediment deposition patterns. The spit accumulates sediment through alongshore sediment transport (AST), while the mainland experiences erosive processes and significant human impacts. The hydrodynamic behaviour and weathering resistance of HMs enables source identification. This has helped to reveal differences between the two regions, with apatite being characteristic of spit sediments and garnet of mainland beaches. Coastal processes, such as erosion, sediment transport, and accumulation, significantly shape the distribution of the HMs, with garnets dominating erosive shores and amphiboles dominating accumulative shores. Furthermore, the study found that human-made coastal infrastructure also affects the composition of HMs and the sediment distribution through AST. This research has implications beyond the local level, providing global insights into the complexities of coastal dynamics. The study emphasises the importance of using HM analysis in conjunction with grain size analysis to understand the distribution of beach sediment composition. It also highlights the significant role of coastal processes, including anthropogenic impacts such as jetty construction or deepening port entrance canals on AST.
CRIS-Team Scopus Importer:2024-06-07
Keywords: Coastal management; Coastal processes; Heavy minerals; Sediment dynamics

Weathering of crystalline bedrock in Sila Massif and Catena Costiera (Calabria, southern Italy) - Caracciolo, Luca; et al. (Rendiconti Online Societa Geologica Italiana, 2012)
Keywords: Clay minerals; Heavy minerals; Soil development; Weathering; X-ray diffraction